Pembuatan Aplikasi Untuk Mencari Solusi Persamaan Diffrensial Linear Orde 1 Dengan Koefisien Tetap - Eliezer Mangoting Rongre; Ottopianus Mellolo; Yoice Rita Putung; Anthoinete Pemina Yece Waroh; Sonny R. Kasenda; Marike Amelda Silvia Kondoj (Prosiding Seminar Nasional Produk Terapan Unggulan Vokasi, 2022)
A research has been done to build an application used to obtain solution of many types of linear different equations of first oder. The research named “Making Aplication For Obtaining Solutions Of First Oder Linear Differential Equations of Constant Coefficient”. The aplication consider five types of differenti alequations . The applications is arranged of five subsprogrms, each for one type of equations. Each subprogram contan of procedures for obtaining general solutions and special of one type of diferential equations, The applications has been tested by compafring tits result with result obtain by manual process. The results are same as the manual result. It is concluded that the application is success.